Integrative transcendental planning in Rawabogo Village with a Hermeneutic approach - Imam Indratno; Alma Verdiana; Raihan Faris Sabil Purawinata (Journal of Sustainable Tourism and Entrepreneurship, 2024)
Purpose: This study aims to design integrative transcendental planning based on exploring phenomena in Rawabogo Village. Since 2011, Rawabogo Village has been designated as a tourism village with customs and cultural heritage. However, the development of tourism village planning has yet to show significant progress. Research Methodology:  Descriptive qualitative with a symbolic and critical hermeneutic approach, which produces integrative transcendental planning. The data is collected through remote observation and understanding of the information unit. Results: The results provide an explanation and understanding that Rawabogo Village has the potential to be developed as a tourism village with the oral traditions of the Mount Nagara Padang site and local cultural life as the main attraction. This attraction must be aligned with stakeholder planning and understanding by sustainably implementing economic, innovation, cultural landscape, and community strategies. This strategy will have implications for tourism village planning in Rawabogo Village. Limitations: The limitation of this research lies in the process of meaning, which is not too deep, and methods can only be implemented in small planning scopes. Contributions: Integrative transcendental planning is a new contribution to the development of village planning and development paradigms because it does not only consider instrumental approaches but also communication and phenomenological approaches that are appropriate for village phenomena. Customs and cultural heritage are a phenomenon with significant potential that needs to be packaged sustainably to become a tourist attraction in Rawabogo Village.